Examination of the viability of co-operative road-vehicle systems using qualitative data analysis - Walta, L.; van Driel, C. J. G.; Krikke, R. H.; van Arem, B. (European Journal of Transport and Infrastructure Research, 2005)
Co-operative road-vehicle systems, such as dynamic navigation and in a later stadium traffic-responsive adaptive cruise control, are expected to contribute to traffic safety and efficiency. However, it is not yet clear which concepts of co-operative systems would be viable from an implementation point of view. Therefore, the objective of the research presented in this paper was to gain knowledge into the expectations about co-operative road- vehicle systems and the driving forces and barriers of stakeholders. To obtain this information, semi-structured interviews were held with six experts and seventeen stakeholders. The qualitative interview data was structured in a database that was used to perform the analysis. Of all the concepts of co-operative road-vehicle systems mentioned by the interview participants, five were recognised as potentially viable: Navigation systems, Intelligent Speed Adaptation (ISA), Traffic responsive Adaptive Cruise Control, Intersection support and Information systems. A deployment path for these systems was constructed based on the two main routes for deployment recognised that focused on Telematics and Advanced Driver Assistance Systems respectively. Two viable concepts were identified at the point where positive expectations about cooperative road-vehicle systems and the driving forces of stakeholders coincided. Obligatory half-open ISA relieves barriers such as market penetration and profitability and is expected to have positive effects on efficiency and safety. A multifunctional information platform would increase efficiency for commercial transportation.